Effect of material model on residual stress and distortion in T-joint welding. (2nd January 2018) - Fu, Guangming; Estefen, Segen F.; Gurova, Tetyana; Lourenco, Marcelo Igor
ABSTRACT: Welding-induced residual stress and distortion have detrimental influences on the ultimate strength of ships and offshore structures. Various experimental and numerical studies have been performed to understand the mechanism of residual stress and distortion under different factors, such as boundary condition, welding sequence and so on. In the present study, experimental tests and numerical simulations were performed to investigate the welding-induced residual stress and distortion under different material models. A sequentially coupled thermo-mechanical finite element model which implemented high temperature effects, temperature-dependent material properties and a moving volumetric heat source was developed to investigate the effect of material model on the residual stress and distortion in T-joint welds. The finite element models were validated carefully by the experimental tests. The results show that the material model has significant effects on residual stress and distortion. Considering that the welding process involves substantial plasticity, the material model must be carefully calibrated.